PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN INDUSTRI JASA BENGKEL (Kasus PT. Mewah Kencana Motor Pekanbaru) - Rajagukguk, Resti Julia; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
PT. Mewah Kencana Motor Pekanbaru is a company engaged in the sale of motorcycles and provides workshop services. In order to face the competition is quite tough, companies should pay attention to the quality of service and maintain their corporate image in order to increase the satisfaction and comfort at this company. For that we perform research on the influence of service quality and corporate image influence on customer satisfaction. This study aims to identify and be able to explain the influence of services and the image given to customer satisfaction at PT. Mewah Kencana Motor Pekanbaru. The population is mostly of customers that come in a period of one year ie in 2014, amounting to 4,296 people. While the sampling technique in this study using accidental sampling with a sample of 98 respondents. Data collection techniques used were questionnaires and interviews, while the data analysis technique used is multiple linear regression. From the analysis of the data found that the independent variable is the quality of service and corporate image each have indicator interrelated positive effect on the dependent variable is customer satisfaction.Keyword : Service Quality, Corporate Image, Customer Satisfaction